Agile Software Development: Adaptive Systems Principles and Best Pract ices - Meso, Peter; Jain, Radhika (Information Systems Management, 2006)
Today's environments of increasing business change require software de velopment methodologies that are more adaptable. This article examines how complex adaptive systems (CAS) theory can be used to increase our understanding of how agile software development practices can be used to develop this capability. A mapping of agile practices to CAS princ iples and three dimensions (product, process, and people) results in s everal recommendations for “best practices” in systems development.
Keywords: IMPORTANT